Relationship between explosive strength and running speed in college soccer players. (Revista horizonte, 2016)
Objective: The objective of this study was to investigate the relationship between 20-meter displacement speed and the explosive force through the vertical counter-movement jump (CMJ). Methods: 30 male college soccer players aged between 18 and 30 years belonging to the soccer team of the San Sebastian University of Concepción Campus were evaluated. They were measured by the vertical jump with countermovement (CMJ) by using a contact-type platform ergo jump and a 20- meter run with electric photo-cell . For data analysis descriptive statistics and Pearson correlation were used. The significance level was p